Pengukuran Produktivitas Tenaga Kerja Pemasangan Plafon U-Baffle menggunakan Metode Time Study dan Productivity Rating - Sasmita, Aurora Anggun; Fiara, Alma; Utama, Agung Bhakti; Islami, Rizky Citra (Politeknik Pekerjaan Umum, 2023)
This study aims to determine the productivity values and Labor Utilization Rate (LUR) of labor in the U-Baffle ceiling installation work. The research sample covers an area of 505 m2. Data normality is controlled using the Upper Control Limit (UCL) and Lower Control Limit (LCL). The results indicate that the productivity value for the installation of the hanging rod is 107.38 m2/day, stringer 138.21 m2/day, hollow (2.5 m) 125.41 m2/day, hollow (4m) 97.08 m2/day, and U-Baffle panel 525.71 m2/day. The coefficient values for craftsmen and workers for frame installation are 0.0268 OH, and for ceiling cover installation are 0.019 OH. The LUR values for craftsmen in the morning and afternoon are 38.48% and 39.2%, respectively. Meanwhile, the LUR values for workers are 42.98% in the morning and 47.11% in the afternoon. From these results, it is concluded that the labor force is not working efficiently, and there is still room for performance improvement, as indicated by LUR values being less than 50%.